The effect of allergic rhinitis on nasal septal body size - San, Turhan; Gürkan, Emre; Erdoğan, Barış; Taşel, Bülent (ENT Updates, 2014)
Objective: To determine whether there is any radiologically detected effect of allergic rhinitis on nasal septal body (NSB) size. Methods: Forty patients previously diagnosed with allergic rhinitis, and randomly selected thirty controls without allergic rhinitis were included in this study. Measurements of NSB size were performed in coronal plane paranasal sinus CT. Patients who had undergone nasal surgery, those with nasal polyposis, patients still using topical nasal spray, oral antihistamines, oral steroids and oral leukotrienes were excluded from the study. Results: The average width of NSB was found 11.2 mm in patients with allergic rhinitis and 10.74 mm in patients without allergic. There was no significant difference between patients with and without allergic rhinitis in terms of NSB size on coronal plane paranasal sinus CT examination. Conclusion: Our results did not support the findings of previous studies. However, further randomized, prospective, controlled trials on larger series are necessary for making more precise interpretations.